Geigeria Alata- a Potential Source for Anti-Alzheimer’s Constituents: In Vitro and Computational Investigations - Wadah Osman; Mohamed A. Maaz; Amna Ali; Eltayeb Fadul; Ahmed H. Arbab; Mosab Yahya Al-Nour; Ahmed Ashour; Asmaa E. Sherif; Hamada S. Abulkhair; Sabrin R.M Ibrahim; Kholoud F. Ghazawi; Gamal A. Mohamed; et al. (Indonesian Journal of Pharmacy, 2023)
Antioxidants and acetylcholinesterase inhibitors play a key role in the prevention and management of degenerative disorders including Alzheimer’s disease in particular. Identifying new anticholinesterases from natural sources may contribute to combating this class of diseases. The present study aimed to evaluate the potential anti-Alzheimer’s activity of Geigeria alata (DC), a plant used in Sudanese folkloric medicine. Accordingly, the whole DC plant extract including twenty phytoconstituents of phenolic, flavonoid, and tannin types was evaluated in vitro as antioxidants and acetylcholinesterase inhibitors. As well, their pharmacokinetics, drug likeliness, and toxicity profiles were assessed. Additionally, the virtual binding of the plant’s phytoconstituents with the cholinesterase target was investigated by docking against two AChE X-ray crystallographic structures. The best effective DPPH radical scavenging activity was demonstrated by both ethyl acetate and n-butanol fractions with percentages of inhibition of 91 ± 0.02% and 90 ± 0.02% (IC50 22 ± 0.01 and 66 ± 0.02 µg/mL), respectively. The ethyl acetate fraction showed statistically significant, and the highest AChE inhibitory activity (78% inhibition, IC50 0.246 ± 0.02 mg/mL). Furthermore, the ethyl acetate fraction exhibited the highest total phenolic, flavonoid, and tannin values. Among identified compounds, quercetin and hispidulin showed promising in silico anti-AChE activity and hence merit further studies for the isolation and characterization of these active constituents.